Female spider aggression is associated with genetic underpinnings of the nervous system and immune response to pathogens. Issue 14 (24th June 2020) - Chang, Chia‐chen; Connahs, Heidi; Tan, Estella Cai Yu; Norma‐Rashid, Y.; Mrinalini,; Li, Daiqin; Chew, Fook Tim
Abstract: Identifying the genetic architecture underlying phenotypic variation in natural populations and assessing the consequences of polymorphisms for individual fitness are fundamental goals in evolutionary and molecular ecology. Consistent between‐individual differences in behaviour have been documented for a variety of taxa. Dissecting the genetic basis of such behavioural differences is however a challenging endeavour. The molecular underpinnings of natural variation in aggression remain elusive. Here, we used comparative gene expression (transcriptome analysis and RT–PCR), genetic association analysis and pharmacological experiments to gain insight into the genetic basis of aggression in wild‐caught jumping spiders ( Portia labiata ). We show that spider aggression is associated with a putative viral infection response gene, BTB/POZ domain‐containing protein 17 (BTBDH), in addition to a putative serotonin receptor 1A (5‐HT1A) gene. Spider aggression varies with virus loads, and BTBDH is upregulated in docile spiders and exhibits a genetic variant associated with aggression. We also identify a putative serotonin receptor 5‐HT1A gene upregulated in docile P. labiata . Individuals that have been treated with serotonin become less aggressive, but individuals treated with a nonselective serotonin receptor antagonist (methiothepin) also reduce aggression. Further, we identify the genetic variants in the 5‐HT1A gene that are associated with individual variation in aggression. We therefore conclude that co‐evolution of the immune and nervous systems may have shaped the between‐individual variation in aggression in natural populations of jumping spiders.